Influence de l'ordinateur sur l'activité d'enseignement. Le cas d'une situation en Technologie au collège - PATRICE LAISNEY; PASCALE BRANDT-POMARES; JACQUES GINESTIÉ (Metaichmio Publications, 2011)
The research focuses on the teaching- learning process about technological education of information and communication technology (ICT). This involves analysing school organizations implemented and the process of transmission - appropriation of knowledge relating to the use of computers by students. This concerns the development process of objects of knowledge, particularly through the construction and handling of artefacts.